Changing the invariant proline-30 of rat and Drosophila melanogaster cytochromes c to alanine or valine destabilizes the heme crevice more than the overall conformation. - Koshy, T I (1990)
Drosophila melanogaster and rat cytochromes c in which proline-30 was converted to alanine or valine were expressed in a strain of baker's yeast, Saccharomyces cerevisiae, where they sustained aerobic growth. The mutations had no significant effect on the spectra or redox potentials but altered drastically the stability of the bond between the methionine-80 sulfur and the heme iron, as judged by four criteria: (i) the alkaline pKa values of the 695-nm band of the ferric form of the mutant proteins decreased by almost 1 pH unit as compared to the wild types; (ii) the acid pKa values increased by 0.5 to 1.2 pH units; (iii) the 695-nm band half-disappeared at temperatures 10-20 degrees C lower in the mutant proteins than in the wild types; and (iv) the 695-nm band of the mutant proteins was susceptible to concentrations of urea that had little influence on their overall structure. The valine-substituted rat cytochrome c had properties intermediate between those of the wild type and the alanine mutant. The destabilized coordinative bond is located in space a long distance from the mutation site. It is suggested that the mutations weaken the hydrogen bond between the carbonyl of residue 30 and the imino group of the imidazole of histidine-18, modifying the bonding of the heme iron by that imidazole, which, in turn, through a trans effect, weakens the bond between the heme iron and the other axial ligand, the sulfur of methionine-80. Alternatively, the effect of the mutations may be propagated allosterically along the peptide chain.